Strategi Pengembangan Organisasi Karang Taruna Melalui Pendekatan Teori Struktur Formal dan Informal” - Feri Setiawan; Fibiani Adharira Prima; Puput Aryani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Karang Taruna is a youth organization that has an important role in supporting social development at the village and sub-district levels. However, various structural and cultural issues often hinder the optimization of the function of this organization. One of the main causes is the mismatch between the formal administrative structure and the informal structure that develops culturally in the community. Therefore, this community service activity aims to develop a strategy for strengthening the Karang Taruna organization through a formal and informal structure theory approach. The method used in this activity is qualitative research with literature studies as the main data collection technique. The results of the activity show that synchronization between the two organizational structures can increase the effectiveness, member participation, and sustainability of the Karang Taruna work program. In addition, strengthening informal leadership and restructuring formal tasks also encourage the creation of a dynamic and adaptive organizational environment. The implications of this service are expected to be a model for developing social organizations based on organizational theory in rural areas.